A study on factors that influence the saving behavior among government servants at Kota Darul Naim, Kota Bharu / Wan Nor Afizah Wan Yusof - Wan Yusof, Wan Nor Afizah (2011)
This paper report is about a study on factors that influence the saving behavior among government servant at Kota Darul Naim, Kota Bharu. There are three independent variables in this study which are purpose, level of income and asset choice. The objective of this study is to know the relationship between purpose,level of income and asset choice with the saving behavior. For this study, the primary data have been used where researcher had distributed 120 questionaires among the government servant at Kota Darul Naim. The data collected have been analyzed using SPSS (Software Package Science Social) and AMOS (Analysis of Moments Structure). To test the significant, researcher used several method in analyzing the data through the comparative fit index (CFI), coefficient of determination, T-test, F-test, multiple regression and frequency distribution. The finding shows that two variables that is level of income and asset choice is not significant with dependent variables. Finding for another variable that is purpose have a relationship with saving behavior